Construction and cellular uptake evaluation of redox-responsive docetaxel prodrug self-assembled nanoparticles. (3rd April 2018) - Ren, Guolian; Chen, Pei; Tang, Jiaqi; Wang, Rongrong; Duan, Shuai; Wang, Ruili; Xie, Yin; Zhang, Shuqiu
Abstract: Docetaxel (DTX) solution has some serious adverse side effects. A redox-responsive DTX prodrug synthesized in our laboratory was used to prepare DTX prodrug self-assembled nanoparticles (DSNPs) with the method of nanoprecipitation. This study aimed at optimizing the formulation to develop stable preparation for the delivery of DTX. Single-factor test was used to evaluate the effects of the preparation concentration of DTX prodrug, stirring speed, the types of stabilizers and temperature on the prescription process of DSNPs. The particle size and polydispersity index were selected as the evaluation indexes. The entrapment efficiency, drug-loading, size distribution and zeta potential were characterized by UPLC and Zetasizer, respectively. The stability and cellular behavior of DSNPs were investigated by Zetasizer, LC–MS/MS and confocal laser scanning microscope, respectively. The particle size, entrapment efficiency and drug-loading of DSNPs were 173.8 ± 1.4 nm, 98.8% ± 0.1%, and 47.8% ± 0.9%, respectively. DSNPs showed good stability during the storage of 30 days, and were taken into the cells in a time-dependent and concentration-dependent manner. The method of nanoprecipitation could be used to entrap DTX. The preparation method was simple, and the quality of DSNPs was stable and reliable. Through the optimization of the formulation, we obtained uniform and stable DSNPs, which could escape from lysosomes of tumor cells. The optimized formulations were stable for intravenous administration. This study could provide scientific support for the development of nano-drug delivery system of small anti-tumor drug.